Enhanced osteoblastic differentiation of parietal bone in a novel murine model of mucopolysaccharidosis type II - Narutoshi Yamazaki; Mari Ohira; Shuji Takada; Akira Ohtake; Masafumi Onodera; Mahito Nakanishi; Torayuki Okuyama; Ryuichi Mashima (Molecular Genetics and Metabolism Reports, 2023)
Mucopolysaccharidosis type II (MPS II, OMIM 309900) is an X-linked disorder caused by a deficiency of lysosomal enzyme iduronate-2-sulfatase (IDS). The clinical manifestations of MPS II involve cognitive decline, bone deformity, and visceral disorders. These manifestations are closely associated with IDS enzyme activity, which catalyzes the stepwise degradation of heparan sulfate and dermatan sulfate. In this study, we established a novel Ids-deficient mice and further assessed the enzyme's physiological role. Using DNA sequencing, we found a genomic modification of the Ids genome, which involved the deletion of a 138-bp fragment spanning from intron 2 to exon 3, along with the insertion of an adenine at the 5′ end of exon 3 in the mutated allele. Consistent with previous data, our Ids-deficient mice showed an attenuated enzyme activity and an enhanced accumulation of glycosaminoglycans. Interestingly, we noticed a distinct enlargement of the calvarial bone in both neonatal and young adult mice. Our examination revealed that Ids deficiency led to an enhanced osteoblastogenesis in the parietal bone, a posterior part of the calvarial bone originating from the paraxial mesoderm and associated with an enhanced expression of osteoblastic makers, such as Col1a and Runx2. In sharp contrast, cell proliferation of the parietal bone in these mice appeared similar to that of wild-type controls. These results suggest that the deficiency of Ids could be involved in an augmented differentiation of calvarial bone, which is often noticed as an enlarged head circumference in MPS II-affected individuals.